M62 - Membrane applications for water reuse - Wong, Joseph, active 2018; Alspach, Brent; Chalmers, Bruce (AWWA manual ;, 2018)
Reverse osmosis (RO) membranes have been used in water reuse since the 1960s, however; the use of membranes in full-scale reuse applications has changed dramatically. The goal for membrane facilities in water reuse applications is finding the balance between cleaning frequency and chemical and energy costs. This manual presents a comprehensive description of the issues related to applying membrane technologies in water reuse projects. In addition, this manual devotes an entire chapter to case studies to showcase a variety of real world applications.